Impact of Good governance Indicators on Green Growth: Evidence from Kazakhstan - Andabayeva, Gulmira; Kakizhanova, Tolkyn; Yerezhepova, Aimankul; Arzayeva, Maiya; Arpabayev, Erkimbek; Sabyrova, Madina (International Journal of Energy Economics and Policy, 2025)
The functioning of the country’s institutions, and ultimately all socio-economic well-being, depends on the effective work of state governance. The state’s involvement has also taken center stage in recent years when it comes to putting rules and programs into place that safeguard the environment and maximize the economical and effective use of minerals. The purpose of the research work is to evaluate effect of six government indicators on some green growth variables of Kazakhstan. For those 3 autoregressive distributed lag models were applied. In the short term, the lag variable of regulatory quality has a positive effect on production-based CO2 intensity, whereas the lag variable of control corruption lowers it. Additionally, the rule of law slows the increase of production-based CO2 intensity. The gap between the values of the lagged variables rule of law and control of corruption has a substantial negative short-term influence on energy intensity per capita. When the lagged factors of political stability, the absence of violence or terrorism, and the control of corruption all rise, so does energy intensity per capita. The rule of law and voice and accountability, two lagged variables, have adverse effects. An rise in the lagged variable significantly reduces the current Energy intensity per capita. The availability of renewable energy is positively impacted by voice and accountability. An increase in the lagged variable Voice and Accountability also significantly slows down the growth of energy intensity per capita in the short term.